Carvacrol, a Plant Metabolite Targeting Viral Protease (Mpro) and ACE2 in Host Cells Can Be a Possible Candidate for COVID-19 - Javed, Hayate; Meeran, Mohamed Fizur Nagoor; Jha, Niraj Kumar; Ojha, Shreesh (Frontiers in Plant Science, 2021)
The recent outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019 resulted in coronavirus disease-19 (COVID-19) pandemic. Coronaviruses are solely accountable for rising mortality and socioeconomic saddle. Presently, there are few repurposed drugs such as remdesivir or favipiravir approved for the treatment of COVID-19, although plasma therapy is also subject to the emergency approval. However, some potential natural treatments and cures have been proposed. Molecules of natural origin showed therapeutic importance such as antiviral, anti-inflammatory and antioxidant activity, and could be useful drug candidate for treating the infections caused by coronavirus. In recent times, essential oils showed promising therapeutic effects against many viral diseases. Carvacrol is one of the essential oils considered as monoterpene phenol and profoundly found in many aromatic plants e.g. thyme and oregano. Its small quantity is being used in food flavouring constituent and preservative. Carvacrol is also used as a fragrance in cosmetic products. A number of research articles published which showed numerous biological actions of carvacrol and its therapeutic potential of clinical significance. In vitro and in vivo studies showed multiple pharmacological properties such as anti-cancer, anti-fungal, anti-bacterial, anti-oxidant, anti-inflammatory, vasorelaxant, hepatoprotective and spasmolytic. The aim of this review is to highlight the various biological and pharmacological properties carvacrol within the scope of COVID-19.